\(\frac{x-1}{5}=\frac{3}{y+4}\)
=> (x - 1)(y + 4) = 3 . 5
=> (x - 1)(y + 4) = 15
x - 1 | 1 | 15 | -1 | -15 | 3 | 5 | -3 | -5 |
x | 2 | 16 | 0 | -14 | 4 | 6 | -2 | -4 |
y + 4 | 15 | 1 | -15 | -1 | 5 | 3 | -5 | -3 |
y | 11 | -3 | -19 | -5 | 1 | -1 | -9 | -7 |
Vậy....
Chứng minh rằng 1/3<1/[n-1].[n+1] với n thuộc z và n>1
\(\frac{x-1}{5}=\frac{3}{y+4}\)
=> (x - 1)(y + 4) = 3 . 5
=> (x - 1)(y + 4) = 15
x - 1 | 1 | 15 | -1 | -15 | 3 | 5 | -3 | -5 |
x | 2 | 16 | 0 | -14 | 4 | 6 | -2 | -4 |
y + 4 | 15 | 1 | -15 | -1 | 5 | 3 | -5 | -3 |
y | 11 | -3 | -19 | -5 | 1 | -1 | -9 | -7 |
Vậy....
Chứng minh rằng 1/3<1/[n-1].[n+1] với n thuộc z và n>1